Yan Giguère : une table, des étoiles - Couëlle, Jennifer (CV Photo)

(untitled) (Les Productions Ciel variable, 1999)
Summary It has never been the aim of art photography to provide simple testimony to the unfurling of daily life - at least, not of its substance, its insipid ordinariness. The photographic image, after all, is only indicative. It is also, and especially, the representation of a reality the contours of which it determines. Without being an aporetic motif of photography, the quotidian never appears as it is; the photographic image reveals its symbolic space. And for Yan Giguère, who walks through life without waiting for events to occur, the happenstances and serendipities of existence are not so much the subject as the background. They are, in a way, the basis for an intent that is ambitious yet treated with poetry and lightness: the portrayal of a quotidian transcended, liberated in a collective unconscious whose main quality is spirituality - that of humanity, its make-up, from Monday to Sunday.